Chô! Chô! Passarinho: a recepção brasileira às expedições científicas alemãs, 1933-1942 - Julião, André Gomes (2016)
Starting at the end of World War I Brazil and Germany developed strong commercial, cultural and scientific relations. However, from 1938 onwards foreign citizens, German in particular, were subjected to political persecution by the Estado Novo government, which saw them as a threat to the nationalistic program launched by Getúlio Vargas. Such change in policy is evident in the extant documents relative to German scientists who came to carry out expeditions in Brazil before or after 1938. Whereas Otto Schulz-Kampfhenkel and Hans Krieg, who arrived in 1935 and 1937, respectively, were enthusiastically welcomed by government officials and the São Paulo and Rio de Janeiro elites, Adolf Schneider and Helmut Sick, who came in 1939, were harassed by the press, the material they collected was confiscated, and after Brazil and Germany severed diplomatic relations, in 1942, they were sent to prison. Schulz-Kampfhenkel and Krieg sought intentionally to break the Brazilian law, but did not receive any punishment, except for the confiscation of the zoological specimens Krieg attempted to export illegally to Germany. Contrariwise, although Schneider had complied with all the procedures required by the Council for Supervision of Artistic and Scientific Expeditions, he was depicted as a spy in the mass media, jailed and eventually expelled from Brazil. Sick, in turn, deeply engaged in his ornithology studies and looking to escape the war in Europe, continued his work of collection, albeit without official permit, until also he was arrested and portrayed as a spy. The contacts they had with Brazilian scientists might have spared Schneider and Sick from persecution in 1939, but their situation became untenable once Brazil declared war on the Axis in 1942